The Evolution of IS Job Skills: A Content Analysis of IS Job Advertisements From 1970 to 1990 - Todd, Peter A.; McKeen, James D.; Gallupe, R. Brent (MIS Quarterly, 1995)
Changes in the knowledge and skill requirements of information systems (IS) positions were examined by analyzing the content of advertisements for IS professionals placed in four major newspapers over the 20-year period 1970-1990. Three types of jobs were examined: programmers, systems analysts, and IS managers. The analysis of the frequency of phrases in these advertisements suggests that job ads for programmers have changed very little—technical requirements remain high, and business and systems knowledge requirements remain relatively low (although the frequency of mention of business requirements has increased somewhat). IS management positions are also relatively stable (as reflected in the makeup of job ads) from the standpoint that business knowledge requirements have remained high, with technical and systems requirements specified less frequently. The greatest transition in specified job requirements over this 20-year period has occurred for systems analysts. Although this is perhaps not surprising, the nature of this transition is. Contrary to expectations, the relative frequency and proportion of stated technical knowledge requirements in ads have increased dramatically, while the relative frequency of business and systems knowledge requirements has actually decreased slightly. These results raise questions concerning the implicit understanding by academics and practitioners alike of the need for business knowledge on the part of systems analysts and other IS professionals. Various interpretations of these findings are provided, and the implications for both education and recruitment are discussed.